Peran Nenek dalam Peningkatan Cakupan ASI Eksklusif di Desa Bangunjiwo Kasihan Bantul - Rahmad Nugroho; Waryana Waryana; Irianton Aritonang (JURNAL NUTRISIA, 2017)
Background: The problem of low exclusive breast feeding achievement in Indonesia is caused by social cultural factors, i.e. the minimal understanding of expecting mother, family, society, and health servant with the exclusive breast feeding. The husband’s and grandmother’s motivation will influence on successful breast feeding. Objective: This study is aimed to reveal the exclusive breast feeding achievement ang the role of grandmother. Method: This is an observational study. The researcher observes the society phenomena in Bangunjiwo Village, Bantul Regency. The subjects of the study are: 1) grandmothers aging ≥ 55 yeras old, 2) breast feeding mothers, and 3) Posyandu cadres. The data are collected by the focus group discussion, detail interview, and documentation.The instruments of the study are FGD, stationaries, tape recorder, and camera. The data are analyzed from the preparation of transcript, data reduction, data presentation, and conclusion. Results: the success of breast feeding is motivated by grandmother’s role, i.e. 1) suggesting, 2) motivating, 3) caring, 4) reminding when mother goes out, 5) giving the stored mother’s milk for working mother, and midwive’s explanation and training for expecting mother. Conclusion: The role of grandmother in exclusive breast feeding will increase: 1) mother’s understanding of breast feeding advantages, 2) mother’s awareness of exclusive breast feeding, and 3) mother’s attitude of exclusive breast feeding. Therefore, a breast feeding mother will be able to increase in practicing exclusive breast feeding by: 1) overcoming obstacles, 2) consuming balanced nutrition, 3) maintaning health and drinking herb. Finally, these will influence the succssful exclusive breast feeding. Keywords: exclusive breastfeeding, The role of grandmother, mother’s attitude